Effects of canola oil on body weight and composition in adults: an updated systematic review and meta-analysis of 32 randomized controlled trials - Abbas Mohtashamian; Masoumeh Mahabady; Fatemeh Bagheri; Hanieh Barghchi; Azadeh Aminianfar (Nutrition Journal)
Abstract Objective We aim to provide an overview and update the current documents regarding the effect of canola oil (CO) compared to other dietary oils on body weight and composition in adults. Methods PubMed, Scopus, Google Scholar, and ISI Web of Science were searched until Sepetember 2024 for randomized clinical trials (RCTs) that assessed the effect of CO on anthropometric measures. Results In this systematic review and meta-analysis thirty-two studies were included. CO consumption significantly increased WHR (MD: 0.003 cm, 95% CI: 0.001, 0.005, P value: 0.003) and significantly decreased BMI (mean difference (MD): -0.127 kg/m2, 95% C: -0.231, -0.024, P value: 0.016) However, it did not significantly affect other anthropometric measures (P > 0.05). Based on subgroup analysis, CO supplementation significantly reduced BW in studies on T2DM patients, with parallel design, on patients over 50 years old and with a dose of more than 30 g/d. It also significantly increased WC in trials with parallel design and on hyperlipidemia patients. In addition, CO supplementation significantly increased WHR in the majority of subgroups. Conclusions Compared to other oil supplementation, CO could decrease BW, BMI and increase WHR, and WC in general or subgroup analysis. Further studies are needed to provide additional insight into how canola oil affects BW and composition in adults.